Kronos : reimagining musical signal processing - Norilo, Vesa (Taideyliopiston Sibelius-Akatemia, 2016)
Musical signal processing is an avenue of creative expression as well as a realm for commercial innovation. Composers require unheard digital instruments for creative purposes, sound engineers apply novel algorithms to further the recording arts, musicologists leverage exotic mathematics for sophisticated music information retrieval, while designers and engineers contribute exciting products to the vibrant scene of amateurs and autodidacts. Signal processor design is luthiery in the digital age. Design of signal processors by musicians is a topic that has attracted a lot of research since the seminal MUSIC III in the 1960s. The activity in this field suggests that the related questions are not satisfactorily resolved. This study presents Kronos, a programming language based on the paradigms of metaprogramming and reactive multirate systems, aimed for expressive, streamlined description of digital musical instruments and sonic transformations.

Musiikillinen signaalinkäsittely on väylä niin luovaan ilmaisuun kuin kaupalliseen tuotekehitykseenkin. Säveltäjät kaipaavat ennenkuulumattomia digitaalisia soittimia, studiotyössä sovelletaan uusia algoritmeja äänentallennuksen taiteen jatkuvaan kehittämiseen, ja musiikintutkijat hyödyntävät erikoistunutta matematiikkaa äänen laskennalliseen analyysiin. Toisaalla suunnittelijat ja insinöörit rakentavat inspiroivia tuotteita alati kasvavalle musiikinharrastajien ja itseoppineiden joukolle. Signaalinkäsittely on digitaaliajan soitinrakennusta. Signaaliprosessorien suunnittelu muusikoiden itsensä toimesta on aihe, jota on tutkittu paljon sitten 1960-luvun, jolloin MUSIC III -järjestelmä kehitettiin Bell-laboratoriossa. Alan aktiivisuus viittaa siihen, että avoimia kysymyksiä on edelleen paljon. Tämä tutkimus esittelee Kronos-ohjelmointikielen, joka perustuu metaohjelmoinnin ja monitahtisten järjestelmien teoriaan, mahdollistaen digitaalisten soittimien ja äänenmuokkauskeinojen ilmaisuvoimaisen ja suoraviivaisen kuvaamisen.
Keywords: ohjelmointi; signaalinkäsittely; fi=musiikkiteknologia|sv=musikteknologi|en=Music Technology|